Erdheim-Chester Disease With Renal Involvement: A Case Report - Ali Kürşat GANİYUSUFOĞLU and Gökşen GÖKŞENOĞLU and Burçin TUNÇ and Nurdan PAKER (Archives of Rheumatology, 2017)
Erdheim-Chester disease is a type of non-Langerhans cell histiocytosis. It is a rare, multisystem disorder with unknown etiology. Heterogeneity of the clinical symptoms makes the diagnosis challenging. On the other hand, knowing the signs and radiological findings of the disease helps to establish a correct diagnosis. In this article, we present a 51-year-old male patient with skeletal and urinary system manifestations who finally underwent right nephrectomy due to renal insufficiency. The diagnosis was suspected by the retroperitoneal infiltrative process and radiological findings of the tubular bones. Erdheim-Chester disease diagnosis was confirmed with CD68(+) CD1a(-) histiocytes detected by immunohistochemical analysis of the nephrectomy specimen.